2023
DOI: 10.1002/cjoc.202300283
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed [4 + 4] Cycloaddition of Homo‐TMM All‐Carbon 1,4‐Dipole Precursors for Construction of Benzofuro[3,2‐b]azocines and Furo[3,2‐b]azocines

Abstract: Comprehensive SummaryWe developed a novel Pd‐catalyzed [4 + 4] cycloaddition of (benzo)furan‐derived azadienes with homo‐TMM all‐carbon 1,4‐dipoles in situ generated from α‐allyl malonate derivatives, affording an array of benzofuro[3,2‐b]azocines and furo[3,2‐b]azocines with good to excellent yields (up to 96%) and exclusive regioselectivities. This methodology featured mild reaction conditions and good functional group tolerance. The synthetic utility was demonstrated by a gram‐scale reaction. Furthermore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…25 In recent years, the assembly of the azocine skeleton through cascade transformations based on [4 + 4] annulation has evolved as a facile and powerful strategy for access to the related useful medium-sized N-heterocyclic molecules. 31,33,35,38,41,44,45,47,49,53…”
Section: Synthesis Of Azocine Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…25 In recent years, the assembly of the azocine skeleton through cascade transformations based on [4 + 4] annulation has evolved as a facile and powerful strategy for access to the related useful medium-sized N-heterocyclic molecules. 31,33,35,38,41,44,45,47,49,53…”
Section: Synthesis Of Azocine Derivativesmentioning
confidence: 99%
“…In recent years, enyne-amides have been employed as a class of precursors of furan- or pyrrole-fused conjugated heterodienes, which have been extensively applied as robust 4-atom annulation synthons for the assembly of various bicyclic heterocycles through [4 + n ] cycloaddition. 39,41,44,45…”
Section: Synthesis Of Azocine Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Deng and co-workers reported that in situ -generated homo-TMM (trimethylenemethane) all-carbon 1,4-dipoles participated in the [4+4] cycloaddition reaction and afforded furo[3,2- b ]azocines containing an eight-membered N-heterocycle skeleton in good to excellent yields. 42 Zhou and co-workers further developed an enantioselective [4+4] cycloaddition reaction using similar substrates, which was the first catalytic asymmetric [4+4] cyclization of aliphatic 1,4-dipoles. 43…”
Section: The Construction Of Eight-membered Nitrogen-heterocycles Thr...mentioning
confidence: 99%
“… 4 However, these dipolar species often lack structural diversity and heterocyclic 1,4-dipoles are seldom studied, hampering the exploration of the (4 + 4) strategy in a broader manner. 5 To address this long-standing challenge, we wondered whether TM-based furyl species could serve as heterocyclic 1,4-dipoles, which would furnish challenging eight-membered cycloadducts with tetrasubstituted furan scaffolds ( Scheme 1c ). In 2008, Zhang and co-workers presented one remarkable study of Au-catalyzed racemic (4 + 2) cycloaddition of 1-(1-alkynyl)-cyclopropyl ketones with indoles, where the alkynyl cyclopropyl ketones serve as the Au-furyl 1,4-dipole precursors.…”
Section: Introductionmentioning
confidence: 99%